3D lattice Boltzmann investigation of nucleation sites and dropwise-to-filmwise transition in the presence of a non-condensable gas on a biomimetic surface. (January 2019) - Guo, Qing; Cheng, Ping
Highlights: Condensation on a biomimetic surface in the presence of NCG is studied. Three preferred nucleation sites are found. Two-stage growth pattern in dropwise condensation is analyzed. Influencing factors on dropwise-to-filmwise transition are investigated. Abstract: Condensation in the presence of non-condensable gas on a biomimetic pillared subcooled surface with hybrid wettability (with hydrophilic top and hydrophobic side and bottom) is investigated using a newly developed 3D multi-component multiphase lattice Boltzmann model. Three preferred nucleation sites with different surface wettability contrasts are found: (i) at the corner of side and bottom hydrophobic surface; (ii) at the center of the bottom hydrophobic surface, and (iii) on the top hydrophilic surface of the pillar. Influencing factors, such as pillar geometrical parameters, subcooling degree and non-condensable gas concentration, on dropwise-to-filmwise condensation transition are examined. For dropwise condensation on a top hydrophilic pillar surface, the droplet undergoes a two-stage growth pattern from "changing contact line" to "constant contact line". Non-condensable gas is found to aggregate near the condensing interface in the vapor phase and at corners of pillar side surface and bottom surface. Increasing pillar width or pillar height (with other geometric parameters remained unchanged), as well as decreasing degree of wall subcooling or non-condensable gas concentration, can delay transition from dropwise to filmwise condensation.